Chemical Composition And In Vitro Antimicrobial Properties Of Phyllanthus Columnaris Stem Bark Tannins Against Oral Pathogens - T. A. M. Othman; Rohazila Mohd Hanafiah; Noor Akmar Nam; Shahida Mohd-Said; Siti Noor Adnalizawati Adnan (Ectodermal Dysplasia Group Turkey, 2024)
Indexed by SCOPUS